Age Cohort Arrest Rates, 1970-1980 - Greenberg, David F. ([Verlag nicht ermittelbar], 1985)
The data for this collection were gathered from the 1970 and 1980 Censuses and the Uniform Crime Reports for 1970 through 1980. The unit of analysis in this data collection is cities. Included are population totals by age group and arrest data for selected crimes by age group for Atlanta, Georgia, Chicago, Illinois, Denver, Colorado, Knoxville, Tennessee, San Jose, California, Spokane, Washington, and Tucson, Arizona. Population data by sex and age for all cities are contained in Part 4. The 123 variables provide data by age categories ranging from age 5 to age 69. Part 1, the arrest file for Atlanta and Chicago, provides arrest data for 1970 to 1980 by sex and age, ranging from age 10 and under to age 65 and over. The arrest data for other cities span two data files. Part 2 includes arrest data by sex for ages 15 to 24 for the years 1970 to 1980. Part 3 provides arrest data for ages 25 to 65 and over for the years 1970, 1975, and 1980. Arrest data are collected for the following crimes: murder, forcible rape, robbery, aggravated assault, burglary, larceny, motor vehicle theft, other assaults, arson, forgery, fraud, embezzlement, stolen property, vandalism, weapons, prostitution, other sex offenses, opium abuse, marijuana abuse, gambling, family offenses, drunk driving, liquor law violations, drunkenness, disorderly conduct, vagrancy, and all other offenses combined.